Application of a knowledge-based expert system for intersection improvement - De Guzman, Mark P.; Sigua, Ricardo G.
The KBES developed is a menu-driven type using open source programs with three very important web development tools: The Apache for web server, MySQL for database management, and PHP (Hypertext Preprocessor) for scripting "C" program language. The system guides the user in selecting exact location of congestion or road crash prone areas through an interface. The user deals with series of questions in identifying the cause of the problem which leads to potential traffic control alternative solutions. The KBES was tested at two local isolated intersections in Quezon City, Philippines for validation. The intersections validated are signalized and unsignalized three-legged intersections. The KBES recommendation for the signalized intersection is to increase right turning radius of the corner pavement for trucks to avoid conflict and delay with other vehicles. For the unsignalized intersection, KBES recommended a left turn prohibition at major approach to avoid delay and collisions at such approach.
Keywords: Knowledge-based expert system; Traffic congestion; Traffic accident; Intersection